Diel variability of thermohaline and carbon system parameters in the sea-surface microlayer and underlying water of a Mediterranean coastal site (Šibenik, Croatia) - Mariana Ribas-Ribas; Ander López-Puertas; Oliver Wurl; Sanja Frka (PANGAEA, 2025)
This dataset includes high-frequency measurements and discrete sampling data collected during a six-day oceanographic campaign conducted in August 2020 near Šibenik, in the Middle Adriatic Sea. The data span three complete diel (24-hour) cycles and focus on the sea-surface microlayer (SML) and underlying water (ULW), to investigate day–night differences in key physicochemical variables related to the inorganic marine carbonate system. The study emphasizes the role of diel variability in air–sea CO? exchange processes.